2017
DOI: 10.1080/02705060.2017.1287129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental features at multiple scales and spatial structure on stream fish communities in a tropical agricultural region

Abstract: Land cover change for agricultural expansion exerts strong pressures on tropical streams. We examined the relative contributions of catchment land cover, local environmental features, and spatial patterns on stream fish communities (n D 43). Explained variation in fish community structure was partitioned (p-RDA) between the explained fractions as follows: pure local 10%, pure catchment 1%, pure spatial 3%, and shared environmental and spatial 7%. Among the possible reasons for the lack of effect of catchment-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
1
10
0
1
Order By: Relevance
“…According to some authors, this relationship between landscape and fish assemblages is indirect and is mediated by instream feature changes (e.g., Iwata et al, 2003;Smokorowski and Pratt, 2007;Pease et al, 2011). If we consider this factor, it is possible that the findings of Roa-Fuentes and Casatti (2017) are mediated by the weakening relationship between landscape features and instream habitat features, as demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…According to some authors, this relationship between landscape and fish assemblages is indirect and is mediated by instream feature changes (e.g., Iwata et al, 2003;Smokorowski and Pratt, 2007;Pease et al, 2011). If we consider this factor, it is possible that the findings of Roa-Fuentes and Casatti (2017) are mediated by the weakening relationship between landscape features and instream habitat features, as demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Terra, Hughes, and Araújo (2016) and Roa-Fuentes and Casatti (2017) found that fish assemblage structure was more influenced by local variables than catchment and spatial variables. However, fish assemblages were more strongly related to local habitat than landscape features.…”
Section: Discussionmentioning
confidence: 90%
“…However, fish assemblages were more strongly related to local habitat than landscape features. Similarly, Terra, Hughes, and Araújo (2016) and Roa-Fuentes and Casatti (2017) found that fish assemblage structure was more influenced by local variables than catchment and spatial variables. In a separate study involving different sites within our study basin, Leal et al (2017) also found that fish assemblages were more strongly associated with local habitat variables than landscape features.…”
Section: Discussionmentioning
confidence: 93%
“…Factors such as the riparian vegetation cover, the availability of refuges and stream flow velocities, which are often referred to as determinants of community structure (Benone et al, 2018;Mendonça, Magnusson, & Zuanon, 2005;Roa-Fuentes & Casatti, 2017), also have a functional effect on the fish assemblages. Factors such as the riparian vegetation cover, the availability of refuges and stream flow velocities, which are often referred to as determinants of community structure (Benone et al, 2018;Mendonça, Magnusson, & Zuanon, 2005;Roa-Fuentes & Casatti, 2017), also have a functional effect on the fish assemblages.…”
Section: The Morphology Of Farlowella Amazonum and Brachyhypopomusmentioning
confidence: 99%